Interaction between neighboring asperities during flattening: A discrete dislocation plasticity analysis. (November 2015) - Sun, Fengwei; Van der Giessen, Erik; Nicola, Lucia
Highlights: The flattening of equispaced surface asperities is studied by dislocation dynamics. Micron-scale asperities are harder to flatten if they are closely spaced. Dislocation limited plasticity is the main cause for this asperity density effect. Abstract: Discrete dislocation plasticity simulations are performed to investigate the role of interaction between neighboring asperities on the contact pressure induced by a rigid platen on a rough surface. The rough surface is modeled as an array of equispaced asperities with a sinusoidal profile. The spacing between asperities is varied and the contact pressure necessary to flatten the surface to a given strain is computed. Plasticity in the asperities and in the crystal below is described by the collective glide of dislocations of edge character. Results show that the mean contact pressure necessary to flatten closely spaced asperities is larger than that required to flatten widely separated asperities. A small dependence on asperity density is already observed for a purely elastic material, but it is enhanced for small asperities, in the presence of dislocation plasticity. Plastic strain gradients, dislocation limited plasticity and interaction between neighboring plastic zones all contribute to what we will call the asperity density effect. Since dislocation limited plasticity plays a dominant role, the asperity density effect will mainly be relevant for surfaces having small asperity roughness.